نظرية القيود ( TOC ) وعلاقتها بتكلفة مخزون المنتجات الزراعية : دراسة تطبيقية - أحمد، محمد عبدالحميد عامر; رزق، محمود عبدالفتاح إبراهيم; باسيلي، مكرم عبدالمسيح (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2017)
Abstract: The Present Study Aimed To Demonstrate The Possibility Of Using The Theory Of Restrictions In Reducing The Cost Of Agricultural Stock. A Survey List Was Directed To Some Agricultural Establishments In Libya To Test The Imposition Of The Study. The Study Concluded That The TOC Approach Helps To Establish A Production Schedule, To Maximize The Efficiency Of Use Of Scarce Resources, And To Establish A Production Schedule To Improve Inventory Accumulation, Thereby Reducing The Cost Of Agricultural Stock. The Study Recommended The Need To Focus On The Introduction Of The Theory Of Constraints (TOC) Especially For Agricultural Establishments In Order To Help Determine The Constraints On The Production Of Optimal Size And The Optimal Combination Of Production, Which Helps To Reduce The Cost Of Stocks For Agricultural Products.
هدفت الدراسة الحالية إلى بيان إمكانية استخدام نظرية القيود في خفض تكلفة مخزون المنتجات الزراعية، وقد تم تصميم قائمة استقصاء تم توجيهها لبعض المنشآت الزراعية في ليبيا، بهدف اختبار فرض الدراسة. وتوصلت الدراسة إلى أن مدخل نظرية القيود (TOC) يساعد على وضع جدول زمني للإنتاج، لتعظيم كفاءة الاستخدام للموارد النادرة، ووضع جدول زمني للإنتاج لتحسين تراكم المخزون بما يؤدي إلى خفض تكلفة مخزون المنتجات الزراعية. وأوصت الدراسة إلى ضرورة التركيز على مدخل نظرية القيود (TOC) خاصة للمنشآت الزراعية وذلك للمساعدة في تحديد القيود على إنتاج الحجم الأمثل والتوليفة المثلى للإنتاج، بما يساعد على خفض تكلفة المخزون للمنتجات الزراعية.
Keywords: نظرية القيود ( TOC ) -- المنتجات الزراعية -- الإنتاج الزراعى -- الاقتصاد الزراعى -- الرسائل الجامعية